THE EXPRESSION OF METABOLIC CHANGES AND FACTORS OF NON-SPECIFIC RESISTANCE IN PATIENTS WITH CHRONIC BRONCHITIS AND COMORBID PEPTIC ULCER AT DIFFERENT TERMS OF TREATMENT AND OUTPATIENT OBSERVATION - Burmak , Yurii; Petrov , Yevhen; Ivanytska , Tetiana; Іvanytskyi , Іgor (Collection of scientific papers «ΛΌГOΣ», 2023)
The process of recovery after treatment of an exacerbation of chronic bronchitis (ChB) with conventional pathogenetic therapy most often proceeds for several weeks, while various residual effects in the form of post-infectious asthenia can be observed, and the presence of comorbidity can negatively affect the course of the disease and contribute to its progression [1]. During the progression of respiratory diseases, there is a violation of phagocytosis with an increase in the activity of pro-inflammatory cytokines [2], the intensity of lipid peroxidation [3, 4] with a decrease on the activity of the antioxidant system [5], and a significant role is played by a violation of the function of the endothelium [6]. The above actively affects the remodeling of the bronchial tract and the development of bronchial obstruction, damage to vessels of various calibers and changes in systemic and microhemodynamics, and in conditions of comorbidity, long-term maintenance of a local inflammatory process which implies the search for ways to correct these changes [7]. We did not exclude the possibility of changes of non-specific immune resistance, the intensity of lipid peroxidation and changes in nitric oxide metabolism in patients with ChB and comorbid peptic ulcers of the duodenum (PDU), the presence of which required timely correction.